The evolutionary characteristics and driving factors of Chinese coastal defense settlements—a case study of Dacheng Suo Citadel - Dan Chen; Zhiyuan Zhong; Yang Chen; Hankun Lin; Xuemei Zhu (Journal of Asian Architecture and Building Engineering)
Wei-suo citadels originated during the Ming Dynasty (1368 – 1644 AD) played a pivotal role in China’s marine military defense system, forming a distinctive component of global maritime military facilities. During the decline of the Ming Dynasty, many Wei-suo citadels transitioned from military fortifications to residential settlements. Today, they represent unique examples of ancient military urban planning and residential environment construction. The Dacheng Suo Citadel has a substantial scale and remarkable authenticity and integrity in terms of preservation. Focusing on it, this study employs systematic diachronic analysis through literature research of local gazetteers and ancient maps, field surveys, and interviews with inhabitants. The development trajectory of Dacheng Suo Citadel encompasses periods of growth, decline, and regeneration. As it transitioned from a military fortress to a settlement, its spatial form exhibited characteristics of central diversification., functional complexity, texture intensification, and boundary blurring. This research offers a scientifically grounded understanding of maritime defense settlements throughout the lifespan of Dacheng Suo Citadel. It provides reliable references for the conservation, tourism development, and daily management of these heritages by uncovering the historical evolution trajectory of its settlement spatial form, identifying complex driving forces, and revealing local historical memory and cultural characteristics.